Rancang Bangun Sistem Monitoring Listrik Tiga Fasa Berbasis IoT pada Bengkel TITL SMKN 1 Tangerang - I Kadek Dwi Adnyano (JASEE Journal of Application and Science on Electrical Engineering, 2026)
Stable electrical parameters are essential for safe and reliable practical activities in vocational electrical workshops. Initial observation at the Electrical Power Installation Engineering workshop of Sekolah Menengah Kejuruan Negeri 1 Kabupaten Tangerang recorded a phase-to-neutral voltage of 190 V, indicating the need for continuous monitoring. This study designed and implemented an Internet of Things-based three-phase electrical parameter monitoring system using a PZEM-6L24 sensor, ESP32 microcontroller, local display, and Blynk platform. The system was developed using the Analyze, Design, Develop, Implement, and Evaluate model and validated through functional testing, laboratory comparison with conventional measuring instruments, and field implementation at the main distribution panel. Laboratory testing of 21 evaluated parameters produced an average error of 1.31%, with a maximum error of 2.33% for current and a minimum error of 0.31% for voltage. Field comparison produced an average error of 1.18%, while all 21 evaluated parameters were displayed successfully in real time. The field snapshot also showed highly uneven phase currents, indicating uneven load distribution under the observed operating condition. The developed system can support real-time electrical monitoring and maintenance evaluation in vocational workshops.